Information contour of the solution of dynamic conflict situations of system of aeronautical service of flights - Сугоняко, Л. М.; Харченко, В. П. (Proceedings of National Aviation University (archive), 2000)
The frame and algorithm of operation of information contour of the solution of dynamic conflict situations is presented. The schedule of development of ground infrastructure of a CNS/ATM is proposed. The offered algorithm allows to reduce influence of the human factor and to optimize the solution of conflict situation